Orbit and intrinsic spin-up of the newly discovered transient X-ray pulsar Swift J0243.6+6124 - Doroshenko V; Tsygankov S; Santangelo A (EDP SCIENCES S A, 2022)
We present the orbital solution for the newly discovered transient Be X-ray binary Swift J0243.6+6124 based on the data from the gamma-ray burst monitor on board Fermi obtained during the October 2017 outburst. We model the Doppler induced and intrinsic spin variations of the neutron star assuming that the latter is driven by accretion torque, and we discuss the implications of the observed spin variations for the parameters of the neutron star and the binary. In particular, we conclude that the neutron star must be strongly magnetized, and estimate the distance to the source at similar to 5 kpc.